2017
DOI: 10.1016/j.engfracmech.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Moving crack with a contact zone at interface of magnetoelectroelastic bimaterial

Abstract: The plane-strain problem of a moving crack at the interface of two dissimilar magnetoelectroelastic (MEE) materials is investigated. Assuming that the crack moves at a constant speed in the subsonic regime, a fracture analysis of a finite crack under concentrated loading imposed onto the crack face is first carried out. By applying magnetoelectric (ME) permeable boundary conditions at the crack face, a combined Dirichlet-Riemann problem is formulated and solved analytically. The expressions for the fracture pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Due to the success of existing fracture mechanics theories in the brittle materials, the studies of static and dynamics cracks problems including mathematical derivations were also extended to fracture in smart materials such as piezoelectric [10][11][12][13][14] and magneto-electro-elastic (MEE) [15][16][17][18][19][20][21][22] materials. MEE materials due to their electro-magnetic-mechanical coupling effect are considered as one of the smart materials and have been extensively used in various smart embedded structures as actuators, transducers and sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the success of existing fracture mechanics theories in the brittle materials, the studies of static and dynamics cracks problems including mathematical derivations were also extended to fracture in smart materials such as piezoelectric [10][11][12][13][14] and magneto-electro-elastic (MEE) [15][16][17][18][19][20][21][22] materials. MEE materials due to their electro-magnetic-mechanical coupling effect are considered as one of the smart materials and have been extensively used in various smart embedded structures as actuators, transducers and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that under impermeable or permeable crack‐face conditions crack velocity has a significant effect on the field intensity factors. The problem of contact zone at interface of MEE bimaterials was extended for a crack moving at a constant subsonic speed by Ma and his co‐workers [21]. Using the solution of the Dirichlet–Riemann problem, the explicit expressions for contact zone length and field intensity factors were evaluated.…”
Section: Introductionmentioning
confidence: 99%